Human Body and its Relation with Planets Siddha Perspective (International Journal of Ayurveda and Pharma Research, 2022)
Siddha system is the foremost traditional system, which was introduced by ancient Siddhar’s. According to Siddhar’s, nature is man, man is nature. Man is said to be microcosm and universe is macrocosm. The universe is made up of five elements namely Earth, Water, Fire, Air, and Space. Our body is also made up of five elements (Panchaboothas), three vital humors known as Vatham (air, space), Pitham (fire), Kabam (Earth, water), seven physical constituents are Saram (nourishing fluid), Senneer (blood), Oonn (muscles), Kozhuppu (adipose tissue), Enbu (bone), Moolai (bone marrow), Sukkilam/Suronitham (sperm/ovum) respectively. The universe has stars and planets. Each planet has an influence that reflects in our bodies. Thoughts were controlled by cosmic force in the universe. Nine planets in the universe correlate with the organs in the body Sun-Heart, Moon-Brain, Mercury-Lungs, Jupiter-Liver, Saturn-Spleen, Mars-Gall Bladder. This article explains how the planets have a connection with our human body.